Confidentiality of company's information: Challenges for nominee director - Hassan, Halyani; Abd Ghadas, Zuhairah Ariff (UPM Press, 2017)
Company directors are subject to certain fiduciary duties discussed under common law and in statutory provisions. Directors’ fiduciary duties include duty to protect the confidentiality of company information. Any information that belongs to the company is to be used only by the company for the company. Such information is considered the property of the company and it must be used to the advantage of the company. The objective of this paper is to discuss the duty of nominee directors concerning the confidentiality of company information. Nominee directors who actually represent their nominators on a board of directors will find their duty challenging as they might be expected by their nominators to provide them with certain company information. The study is based on doctrinal and statutory analysis of selected jurisdiction as well as cases based on various jurisdiction. It is argued that nominee directors are in a vulnerable position as directors who are representing their nominators at the same time. Though it has been clearly legislated that their loyalty is to the company they should to a certain extent be allowed to disclose information that would not jeopardise their companies.